(untitled) (Nigerian Journal of Physiological Sciences, 2021)
There is increased possibility that combined herbal constituents may interact to increase toxicity and lower efficacy. Ruzu herbal bitters (RHB) is a blend of extracts from Curculigo pilosa, Uvaria chamae, and Citrullus colocynthis, each of which has been shown to possess important bio-effects. There is anecdotal evidence for efficacy of RHB in neurological disorders; however, there are no data on possible neurotoxic effects of RHB. Using behavioural, biochemical and molecular indices as surrogates of neurotoxicity, this study therefore evaluated the nervous system effects of RHB. Twenty male Wistar rats were divided into two groups – a control group and RHB group (n=10). RHB (0.5ml/kg) was administered to the RHB group twice daily while control group took water (0.5ml/kg). Treatments lasted 6 weeks after which behavioural tests were carried out. Animals were subsequently sacrificed and the expression of serotonin transporter (SERT) and dopamine transporter (DAT) was determined in the striatum by immunofluorescence while specific activities of catalase, alkaline phosphatase and gamma glutamyltransferase were determined. In the elevated plus maze and light and dark box tests which are models of anxiety, animals treated with RHB showed significant anxiety compared to control. They also showed impaired locomotor activity in the open field and wire hang tests. The activity of catalase was significantly increased in the brain of the RHB treated rats while an increase in the expression of both DAT and SERT was observed in the striatum